Empowerment strategies of the Mentor Mother peer support program among mothers who have migrated to Sweden: a photovoice study - Per Kåks; Mats Målqvist; Mark Tomlinson; Linnea Stansert Katzen (BMC, 2024)
Abstract Introduction A peer support intervention using 'Mentor Mothers' was implemented for mothers who had migrated to Sweden, living in socially disadvantaged communities. The Mentor Mothers had a high degree of freedom to develop strategies for facilitating empowerment of their clients according to perceived needs. This study aimed to investigate which empowerment facilitation strategies that Mentor Mothers perceived to be relevant, feasible and effective. Methods Photovoice was used to generate qualitative data. Participants took photographs of their work which were then discussed during a focus group discussion and six individual semi-structured interviews. Data were analysed using thematic analysis. Results Four overarching strategies to facilitate empowerment were identified, corresponding to distinctive perceived needs in the target group: (1) Informative support responded to a need for making sense of the external context, by helping mothers navigate society, the process of parenthood and cultural parenting norms. (2) Practical support addressed a need for managing challenges in daily life, by facilitating contacts with welfare services and authorities and to enhance parenting practices. (3) Psychosocial support addressed a need for improved mental wellbeing, by instilling feelings of safety and security in daily life, relationships and in contacts with public institutions. (4) Motivational support responded to a need for finding fulfilling purpose, by promoting social interaction, encouraging civic engagement and sharing the challenges and successes of others to inspire hope. Conclusions These results highlight various aspects of peer support for empowerment facilitation that future interventions targeting immigrant parents can use in their intervention design.